EFEKTIVITAS PEMANFAATAN BANTARAN TUKAD BADUNG SEBAGAI RUANG TERBUKA PUBLIK DI KOTA DENPASAR - I Gusti Made Ananda Putra; I Gusti Putu Anindya Putra; I Nyoman Harry Juliarthana (UNHI PRESS, 2021)
The city of Denpasar has made a new public open space arrangement by utilizing the existing space, in the form of the arrangement of the Tukad Badung riverbank at Kumbasari Park in Denpasar City. The activities carried out are recreation and as a forum for interaction for the community. Because of the phenomenon of using the Tukad Badung riverbank as a forum for interaction and community activities, it is therefore important to see the level of effectiveness and the dominant factors used in measuring the effectiveness of using the Tukad Badung bank as an open space public. The effectiveness of good utilization of public open space can be seen from the characteristics of space users and the characteristics of activities as an approach. The research data were obtained through observation, questionnaires, interviews, documentation, and agency surveys. Data analysis used qualitative descriptive analysis techniques with the Good Public Space Index method approach. The results showed the level of effectiveness of the use of the Tukad Badung riverbank as a public open space in Denpasar City at a value of 0.70 which is included in the